Intrusions of autobiographical memories in individuals reporting childhood emotional maltreatment - van Harmelen, Anne-Laura (Co-Action Publishing, 2011)
BACKGROUND: During childhood emotional maltreatment (CEM) negative attitudes are provided to the child (e.g., “you are worthless”). These negative attitudes may result in emotion inhibition strategies in order to avoid thinking of memories of CEM, such as thought suppression. However, thought suppression may paradoxically enhance occurrences (i.e., intrusions) of these memories, which may occur immediately or sometime after active suppression of these memories. OBJECTIVE: Until now, studies that examined suppressive coping styles in individuals reporting CEM have utilized self-report questionnaires. Therefore, it is unclear what the consequences will be of emotion inhibition styles on the intrusion of autobiographical memories in individuals reporting CEM. METHOD: Using a thought suppression task, this study aimed to investigate the experience of intrusions during suppression of, and when no longer instructed to actively suppress, positive and negative autobiographical memories in individuals reporting Low, Moderate, and Severe CEM compared to No Abuse (total N=83). RESULTS: We found no group differences during active suppression of negative and positive autobiographical memories. However, when individuals reporting Severe CEM were no longer instructed to suppress thinking about the memory, individuals reporting No Abuse, Low CEM, or Moderate CEM reported fewer intrusions of both positive and negative autobiographical memories than individuals reporting Severe CEM. Finally, we found that intrusions of negative memories are strongly related with psychiatric distress. CONCLUSIONS: The present study results provide initial insights into the cognitive mechanisms that may underlie the consequences of childhood emotional maltreatment and suggests avenues for successful interventions.